Hubungan Antara Gaya Kelekatan Dengan Homesickness Pada Santri Di Madrasah Tsanawiyah Pondok Pesantren Ihya Ulumiddin - Rindi Aryani Yusuf; Vella Fitrisia Agustina; Mira Rizki Wijayani (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to examine the relationship between attachment style and homesickness among students at Madrasah Tsanawiyah Pondok Pesantren Ihya Ulumiddin. The research uses a quantitative approach. Two scales are employed: the Attachment Style Questionnaire (ASQ) by Feeney et al. (1994) to measure the attachment style variable, and the Utrecht Homesickness Scale (UHS) by Stroebe et al. (2002) to measure the homesickness variable. The population in this study consists of all male and female students in the seventh grade residing at Pondok Pesantren Ihya Ulumiddin, totaling 119 research subjects. The sampling technique used is total sampling (saturation sampling). The analysis results show that the Pearson product-moment correlation coefficient between attachment style and homesickness is r = 0.419 with a p-value of 0.000 (p<0.05), indicating a significant relationship between attachment style and homesickness among students at Madrasah Tsanawiyah Pondok Pesantren Ihya Ulumiddin. Furthermore, differences were found in the relationship between each type of attachment style and the homesickness variable: secure attachment style has a significant negative relationship with homesickness (r = -0.294, p<0.05), while avoidant attachment style (r = 0.465, p<0.05) and anxious/ambivalent attachment style (r = 0.320, p<0.05) show a significant positive relationship with homesickness.